Op soek na ’n gebalanseerde beeld van H.F. Verwoerd - Johannes D. Froneman (Koers : Bulletin for Christian Scholarship, 2013)
Towards a balanced view of H.F. Verwoerd. Doctor H.F. Verwoerd is possibly the most controversial political figure in South African history. In life he was revered by his followers, but even critics acknowledged his stature. Today he is mostly depicted as a brutal symbol of racial suppression. This article first gives insight into various, contradictory views expressed in the press on Verwoerd during his life, immediately after his death and in recent years. This is discussed in view of some media-theoretical perspectives. It is followed by an overview of views expressed on Verwoerd in literature, including recent works by eminent historian Hermann Giliomee. Against this background of diverse and sometimes one-sided views, J.J. (Ponti) Venter’s analysis of Verwoerdian thought, as published in a 1999 issue of Koers – Bulletin for Christian Scholarship, is presented as an example of a balanced intellectual contribution to an ongoing debate. It is argued that Venter’s contribution was important as it provides incisive criticism of Verwoerd not found elsewhere. Venter’s article, which was based on texts of speeches, however lacks some context. This is provided by other publications and press coverage. It is suggested that no assessment of an important historical figure is ever definitive, least so by consulting only the press. As is the case with Verwoerd, contemporaneous press coverage needs to be supplemented by solid research on the subject. In particular the sober analysis of public intellectuals such as J.J. Venter is needed and should be included in assesments of Verwoerd.